2019
DOI: 10.1155/2019/1453612
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavanone as a Potent Antioxidant Isolated from Chromolaena odorata L. Leaves

Abstract: Chromolaena odorata L. (Asteraceae) is one of the tropical plants which is widely used as traditional medicines for diabetes and soft tissue wounds treatment in some regions in East Indonesia. The present study was aimed at determining the bioactive compounds of C. odorata leaves. The methanol and ethyl acetate extracts of C. odorata leaves have the inhibitory activity against 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals as well as α-glucosida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
4
23
0
2
Order By: Relevance
“…Therefore, to support the result of interviewing, the writers spread questionnaire to assess the level of postpartum mother's knowledge on the composition of traditional herbal medicine for postpartum which is consumed and the benefits of every kind of traditional herbal medicine they make. Based on the questionnaire of postpartum mother's knowledge on the composition of traditional herbal medicine shows that they have lower knowledge of traditional herbal medicine and every concoction of traditional herbal medicine for postpartum [4]. Besides, supported by observation result, where during field observation, the writers found there were only 3 from 10 respondents prepared this traditional herbal by them self.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, to support the result of interviewing, the writers spread questionnaire to assess the level of postpartum mother's knowledge on the composition of traditional herbal medicine for postpartum which is consumed and the benefits of every kind of traditional herbal medicine they make. Based on the questionnaire of postpartum mother's knowledge on the composition of traditional herbal medicine shows that they have lower knowledge of traditional herbal medicine and every concoction of traditional herbal medicine for postpartum [4]. Besides, supported by observation result, where during field observation, the writers found there were only 3 from 10 respondents prepared this traditional herbal by them self.…”
Section: Resultsmentioning
confidence: 86%
“…Pengujian fitokimia ekstrak daun serapoh secara kuantitatif menunjukkan bahwa ekstrak etil asetat memiliki kandungan total fenol yang lebih tinggi (212,8 mg/g) dibanding ekstrak dengan pelarut yang lain (Tabel 2). Putri & Fatmawati (2019) juga melaporkan hal yang sama bahwa kandungan total fenol yang lebih tinggi diperoleh dari ekstrak etil asetat dibandingkan pelarut lain yaitu diklorometan, metanol, akuades, dan nheksan. Total flavonoid yang diperoleh dari keempat ekstrak bervariasi dari 8,1 mg/g sampai 195,5 mg/g.…”
Section: Hasil Dan Bahasan Hasil Ekstraksi Dan Analisis Fitokimiaunclassified
“…kaempferol-3-O-gentiobioside and kaempferol-3-O-d-glucopyranoside) have been reported in the leaves of Senna alata [22]. Chromolaena odorata was described to contain polyphenols like flavanone compounds [23]. Previous studies reported the presence of flavonoids in the aqueous and methanolic extracts of Mitracarpus villosus [24].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Previous studies reported the antioxidant capacities of some of studies plants. Chromolaena odorata was described to be a species with antioxidant capacities related to its flavanone compounds [23]. Phenolic compounds such as astragalin, luteolin and diterpenoids compounds were identified to be responsible of antioxidant activity of Tetradenia riparia [26].…”
Section: Antioxidant Activitymentioning
confidence: 99%